Community approval required for periconceptional adolescent adherence to weekly iron and/or folic acid supplementation: a qualitative study in rural Burkina Faso - Adélaïde Compaoré; Sabine Gies; Bernard Brabin; Halidou Tinto; Loretta Brabin (BMC, 2018)
Abstract Background Iron deficiency remains a prevalent adolescent health problem in low income countries. Iron supplementation is recommended but improvement of iron status requires good adherence. Objectives We explored factors affecting adolescent adherence to weekly iron and/or folic acid supplements in a setting of low secondary school attendance. Methods Taped in-depth interviews were conducted with participants in a randomised, controlled, periconceptional iron supplementation trial for young nulliparous women living in a rural, malaria endemic region of Burkina Faso. Participants with good, medium or poor adherence were selected. Interviews were transcribed and analysed thematically. Results Thirty-nine interviews were conducted. The community initially thought supplements were contraceptives. The potential benefits of giving iron supplementation to unmarried "girls" ahead of pregnancy were not recognised. Trial participation, which required parental consent, remained high but was not openly admitted because iron supplements were thought to be contraceptives. Unmarried non-school attenders, being mobile, were often sent to provide domestic labour in varied locations. This interrupted adherence - as did movement of school girls during vacations and at marriage. Field workers tracked participants and trial provision of free treatment encouraged adherence. Most interviewees did not identify health benefits from taking supplements. Conclusions For success, communities must be convinced of the value of an adolescent intervention. During this safety trial, benefits not routinely available in iron supplementation programmes were important to this low income community, ensuring adolescent participation. Nevertheless, adolescents were obliged to fulfil cultural duties and roles that interfered with regular adherence to the iron supplementation regime. Trial Registration Trial Registration at clinicaltrials.gov: NCT01210040.